Pengelompokan Daerah Provinsi Kepulauan Indonesia Berdasarkan Karakteristik Ekonomi dan Potensi Perikanan Tahun 2020 - Ardini Ardini (Seminar Nasional Official Statistics, 2022)
As an archipelagic with wide seas it becomes a defiance for Indonesia in regional development, especially for the archipelagic province. Equitable development depends on the precisely identification regional characteristics, so necessary to group regions that have similar characteristics. This research is clustering based on the economic characteristics and fishery potential in the archipelago province in 2020. With the Fuzzy C-Means method, each object has opportunity to occupy each cluster with membership degree to avoid overlapping clusters. The results is are 4 clusters that stop at the 145th iteration. The classification, cluster 1 is a low of economic area and fishery potentioal consist of 27 members, cluster 2 is a high of economic area and fishery potential consist of 28 members, cluster 3 is a medium economic area and high fishery potential consists of 17 members, and cluster 4 is an area of moderate economy and high fishery potential consisting of 27 members.